Social cognition abilities in patients with primary and secondary chronic pain - Telesca, Alessandra; Vergallito, Alessandra; Consonni, Monica; Mattavelli, Giulia; Ferrario, Alessia; Grazzi, Licia; Usai, Susanna; Romero Lauro, Leonor Josefina (Frontiers in Psychology, 2024)
Previous evidence suggested that chronic pain is characterized by cognitive deficits, particularly in the social cognition domain. Recently, a new chronic pain classification has been proposed distinguishing chronic primary pain (CPP), in which pain is the primary cause of patients’ disease, and chronic secondary pain (CSP), in which pain is secondary to an underlying illness. The present study aimed at investigating social cognition profiles in the two disorders. We included 38 CPP, 43 CSP patients, and 41 healthy controls (HC). Social cognition was assessed with the Ekman-60 faces test (Ekman-60F) and the Story-Based Empathy Task (SET), whereas global cognitive functioning was measured with the Montreal Cognitive Assessment (MoCA). Pain and mood symptoms, coping strategies, and alexithymia were also evaluated. Correlations among clinical pain-related measures, cognitive performance, and psychopathological features were investigated. Results suggested that CSP patients were impaired compared to CPP and HC in social cognition abilities, while CPP and HC performance was not statistically different. Pain intensity and illness duration did not correlate with cognitive performance or psychopathological measures. These findings confirmed the presence of social cognition deficits in chronic pain patients, suggesting for the first time that such impairment mainly affects CSP patients, but not CPP. We also highlighted the importance of measuring global cognitive functioning when targeting chronic pain disorders. Future research should further investigate the cognitive and psychopathological profile of CPP and CSP patients to clarify whether present findings can be generalized as disorder characteristics.